Nanozyme-armored natural enzymes for acute kidney injury management via inflammation regulation and oxidative damage mitigation - Wang, Juntao; Li, Ruifeng; Fu, Xiaofei; Huo, Shuai; Wang, Lijiao; Shao, Fengmin; Gu, Yue (Frontiers in Pharmacology, 2025)
BackgroundAcute kidney injury (AKI) is a major global disease with a complex pathogenesis and a lack of safe and effective radical treatments. Reactive oxygen species (ROS) and inflammation are key drivers of AKI, making antioxidant and anti_inflammatory strategies promising. This study designed a stable nanozyme to simultaneously scavenge ROS and control inflammation.MethodsUsing a biomimetic mineralization approach, catalase (CAT) was immobilized on manganese_based metal sulfide to construct the CAT@MnS nanozyme. In vitro experiments were conducted to assess its antioxidant activity and protective effect on HEK293 cells. In vivo, cisplatin_ and rhabdomyolysis_induced AKI mouse models were used to evaluate renal targeting, ROS_scavenging capacity, and anti_inflammatory efficacy.ResultsIn vitro, CAT@MnS effectively scavenged ROS and protected HEK293 cells from oxidative stress. In vivo, it accumulated in kidneys, reduced renal ROS, lowered inflammatory cytokine levels, and alleviated kidney damage in both AKI models.DiscussionThis study successfully developed a CAT@MnS nanozyme that integrates ROS scavenging with inflammation regulation. The biomimetic mineralization strategy enhanced the stability and therapeutic synergy of the system. The nanozyme offers a new approach for the synergistic treatment of AKI and shows promising potential for translational application.